2013
DOI: 10.1371/journal.pone.0078641
|View full text |Cite
|
Sign up to set email alerts
|

RB1 Status in Triple Negative Breast Cancer Cells Dictates Response to Radiation Treatment and Selective Therapeutic Drugs

Abstract: Triple negative breast cancer (TNBC) includes basal-like and claudin-low subtypes for which only chemotherapy and radiation therapy are currently available. The retinoblastoma (RB1) tumor suppressor is frequently lost in human TNBC. Knockdown of RB1 in luminal BC cells was shown to affect response to endocrine, radiation and several antineoplastic drugs. However, the effect of RB1 status on radiation and chemo-sensitivity in TNBC cells and whether RB1 status affects response to divergent or specific treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 64 publications
5
62
0
Order By: Relevance
“…The other three cell lines were confirmed to be insensitive to the drug, and no pRb was detected in them. This was consistent with the reported loss of RB1 locus in DU4475 and HDQP1 cells (Robinson et al , ) and with its mutation in CAL85‐1 cells as described in the canSAR database (Tym et al , ). The predicted presence or absence of CDK4 phosphorylation was consistent with its detection in these cell lines except for CAL120.…”
Section: Resultssupporting
confidence: 91%
“…The other three cell lines were confirmed to be insensitive to the drug, and no pRb was detected in them. This was consistent with the reported loss of RB1 locus in DU4475 and HDQP1 cells (Robinson et al , ) and with its mutation in CAL85‐1 cells as described in the canSAR database (Tym et al , ). The predicted presence or absence of CDK4 phosphorylation was consistent with its detection in these cell lines except for CAL120.…”
Section: Resultssupporting
confidence: 91%
“…We noted that MDA-MB-468 cells were more radiosensitive than MDA-MB-231 and Hs578T cells (Figure 3C), which is consistent with the findings by other groups [36, 37]. It has been reported that the status of the retinoblastoma tumor suppressor (pRB) in TNBC cells dictates response to radiation treatment, and that pRB-negative TNBC cell lines such as MDA-MB-468 and BT549 are highly sensitive to IR compared to pRB-positive TNBC cell lines such as MDA-MB-231 and Hs578T [37].…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that the status of the retinoblastoma tumor suppressor (pRB) in TNBC cells dictates response to radiation treatment, and that pRB-negative TNBC cell lines such as MDA-MB-468 and BT549 are highly sensitive to IR compared to pRB-positive TNBC cell lines such as MDA-MB-231 and Hs578T [37]. The E2F1 transcription factor is a key downstream target of pRB, and a potent and specific inhibitor of Wnt/β-catenin signaling in colorectal cancer cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…Robinson, et al have also demonstrated that RBnegative TNBC cell lines are highly sensitive to gammairradiation and moderately more sensitive to doxorubicin and methotrexate compared to RB-positive TNBC cell lines (Robinson et al, 2013). In contrast, RB1 status do not affect sensitivity of TNBC cells to multiple other drugs including cisplatin (CDDP), 5-fluorouracil, idarubicin, epirubicin, PRIMA-1met, fludarabine and PD-0332991, some of which are used to treat TNBC patients (Jiao et al, 2014) Aldehyde dehydrogenase 1 (ALDH1): The stem cell marker ALDH1 has been of particular interest to scientists since it has been successfully used as a reliable marker to isolate cancer stem cells from breast cancers.…”
Section: Biomarkers For Targeted Therapymentioning
confidence: 98%
“…The retinoblastoma (RB1) tumor suppressor is deleted or rearranged in ~20-25% of BC cell lines (Wang et al, 1993;Herschkowitz et al, 2008) and is frequently lost in human TNBC (Robinson et al, 2013); It is therefore DOI:http://dx.doi.org/10.7314/APJCP.2016.17.4.1595 important to determine the effect of RB1 status in TNBC lines on response to therapy. Robinson, et al have also demonstrated that RBnegative TNBC cell lines are highly sensitive to gammairradiation and moderately more sensitive to doxorubicin and methotrexate compared to RB-positive TNBC cell lines (Robinson et al, 2013).…”
Section: Biomarkers For Targeted Therapymentioning
confidence: 99%